Neutron-induced reactions investigated via the Trojan Horse Method. (August 2019) - Spartá, R; Spitaleri, C; Lamia, L; Guardo, G L; Cherubini, S; Gulino, M; La Cognata, M; Pizzone, R G; Rapisarda, G G; Romano, S; Sergi, M L; Tumino, A
Abstract: The Trojan Horse Method has been applied to many neutron-induced reactions using the deuteron as a virtual source of neutrons, to explore wide energy regions of interest for astrophysics and applied physics and to investigate the suppression of the centrifugal barrier, that is one of the key advantages of this Method. The neutron-induced experimental campaign has already concerned 17 O(n, α) 14 C, 6 Li(n, α) 3 H, 7 Be(n, p) 7 Li, 7 Be(n, α) 4 He, 18 F(n, α) 15 O and 14 N(n, p) 14 C, and very recently 25 Mg(n, α) 22 Ne and 27 Al(n, p) 27 Mg, while others are planned to be measured soon, thus influencing different astrophysical scenarios. Particular attention is dedicated to a new measurement regarding the 10 B(n, α) 7 Li reaction, aimed to disentangle the 7 Li ground state contribution from its first excited state to the cross section.